KINERJA POMPA AIR TENAGA SURYA (PATS) DENGAN MENGGUNAKAN POMPA DC 12 VOLT 180 WATT - Syaief, Adhiela Noer; Putra, Muhammad Rezky Fitri; Ivana, Reza Taufiqi; Artika, Kurnia Dwi; Isworo, Hajar (POLITALA PRESS, 2023)
The availability of solar energy has great potential for application in the agricultural sector. Electrical power from photovoltaic cells or solar panels mainly depends on sunlight at certain times. The use of this technology can be applied to pump drives in agricultural irrigation systems. In this research, we try to measure a certain time with the efficiency of components from using solar photovoltaic (SPV) with the water discharge produced by the pump on these components. From the experimental results, it was found that the best efficiency was at 14.00 WITA with an efficiency of 57% with the panel facing directly to the sun. From pump testing, it was found that the average water flow was 20.95 liters/minute. From these performance tests, Indonesia itself has sufficient levels of solar radiation to use solar panels as an alternative to sustainable resource.